4
$\begingroup$

Does anyone know how o compute the following limit?

$$\lim_{x\to \infty}x\ \log\left(\frac{x+c}{x-c}\right)$$

I tried to split it up as follows:

$\lim_{x\to \infty}\left[x\ \log(x+c)-x\ \log(x-c)\right]$ but still this is indeterminate form of type $\infty-\infty$. Any thoughts please?

$\endgroup$
  • 1
    $\begingroup$ $$\frac{x+c}{x-c} = \frac{1 + \frac{c}{x}}{1-\frac{c}{x}}$$ $\endgroup$ – Daniel Fischer Nov 16 '14 at 23:47
4
$\begingroup$

Using L'Hospital:

$$\lim_{x\to \infty}x\ \log\left(\frac{x+c}{x-c}\right)=\lim_{x\to \infty}\frac{\log\left(\frac{x+c}{x-c}\right)}{\frac 1x}\underbrace{=}_{\mathrm{L'Hospital}} \lim_{x\to \infty} \frac{\frac{x-c}{x+c}\cdot \frac{-2c}{(x-c)^2}}{-\frac {1}{x^2}}=\lim_{x\to \infty} \frac{x-c}{x+c}\cdot \frac{2cx^2}{(x-c)^2}=2c$$

Without using L'Hospital:

$$\lim_{x\to \infty}x\ \log\left(\frac{x+c}{x-c}\right)=\lim_{x\to \infty} \log\left(1+\frac{2c}{x-c}\right)^x=\log \lim_{x\to \infty}\left(1+\frac{2c}{x-c}\right)^x\\=\log \lim_{x\to \infty}\left(\left(1+\frac{2c}{x-c}\right)^{x-c}\right)^{\frac{x}{x-c}}=\log e^{2c}=2c.$$

$\endgroup$
  • 1
    $\begingroup$ In the second expression in the "without" section, that should be $1+\frac{2c}{x-c}$, not minus. That will make the second answer the same as the first. $\endgroup$ – Rory Daulton Nov 17 '14 at 0:02
  • $\begingroup$ @RoryDaulton Fixed. Thank you for noticing it. $\endgroup$ – mfl Nov 17 '14 at 0:12
4
$\begingroup$

We have:$$\lim_{x\to \infty}x\ \log\left(\frac{x+c}{x-c}\right) = \lim_{x\to \infty}\ \log\left(\frac{x+c}{x-c}\right)^x = \log \lim_{x \to +\infty}\left(\frac{1+\frac{c}{x}}{1-\frac{c}{x}}\right)^x = \log \lim_{x \to +\infty} \frac{\left(1+\frac{c}{x}\right)^x}{\left(1-\frac{c}{x}\right)^x}$$

Using the fundamental limit for $e$: $$= \log \frac{e^c}{e^{-c}} = \log e^{2c} = 2c.$$

$\endgroup$
2
$\begingroup$

Let $u = \dfrac{c}{x}$, then:

Note that: $x\log\left(\dfrac{x+c}{x-c}\right) = c\dfrac{\log\left(\dfrac{1+u}{1-u}\right)}{u} = c\left(\dfrac{\log(1+u)}{u} - \dfrac{\log(1-u)}{u}\right) \to c(1-(-1)) = 2c$ since $x \to \infty \iff u \to 0$.

$\endgroup$
0
$\begingroup$

Hint; Let $t=\frac1x$${}{}{}{}{}{}{}{}{}{}{}{}{}{}{}{}{}{}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.